From the field to the classroom: ESP practitioners’ contributions to ESP teacher education - Murtafi'ah, Banatul (Universitas Islam Indonesia, 2025)
The involvement of practitioners in academia is currently trending in Indonesian Higher Education (HE), including in the English Language Education Department (ELED). English for Specific Purposes (ESP) is a field in English language teaching that is closely related to industry. Some studies have discussed the role of practitioners at HE, but few of them discuss the involvement of professional ESP practitioners in ESP teacher education at universities. To fill this gap, this study aims to investigate the contributions of ESP practitioners to ESP teacher education at the ELED. This present study was a case study based on a 14-week onsite ESP course involving 19 students from the English Language Education Department and one experienced English for Cruise Ship practitioner. This is a qualitative study in which the data were collected from students’ reflective essays. The collected data were then analyzed thematically. This study has revealed four contributions that the practitioner has to academia, i.e., 1) bringing real-world experiences to the classroom, 2) bridging the gap between theory and practice in ESP assessment, 3) creating an engaging learning environment, and 4) helping students prepare for their future careers. This study not only explains how practitioners contribute to ESP teacher education but also recommends a pedagogical implication that could enhance the contribution of practitioners to ESP teacher education.